Ribā in The Qur’an and The Bible: Comparative Legal-Ethical Perspectives on Economic Justice - Rosidin, Khulafaur; Solahuddin, Ahmad (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2025)
Abstract: The prohibition of ribā is a classic issue across religious traditions and remains relevant in contemporary debates on financial practice. This study aims to reinterpret the prohibition of ribā in the Qur’an and the Bible in order to formulate ethical and legal criteria applicable to modern financial instruments. Ma’na-cum-maghza is used as an approach to reinterpret the meaning of riba.. The first stage reconstructs the textual and contextual meanings of key verses. The second stage builds an analytic bridge through classical and modern exegetical findings. The third stage articulates the substantive message (maghzā) as a basis for evaluating financial practices. The findings show that the ethical core of the prohibition of ribā lies in the principle of neither wronging others nor being wronged. This principle rejects forms of interest or gain that are exploitative and that unduly burden debtors, while preserving the specificity of ribā as an ethical and legal category that cannot be reduced to a flat equivalence with interest. The study proposes practical indicators for assessing the ethical validity of contracts, which include fairness in exchange, proportionality between risk and return, protection of vulnerable parties, prevention of burdensome debt spirals, and transparency of information and costs. These results reaffirm the orientation of maqāṣid al-sharīʿah, with particular emphasis on the protection of wealth, and offer a cross-scriptural evaluative framework that can be adopted in the design of contemporary Islamic financial contracts and policies. Abstrak: Larangan riba merupakan isu klasik lintas tradisi agama yang tetap relevan dalam diskusrsus praktik keuangan modern. Penelitian ini bertujuan menafsirkan ulang larangan riba dalam Al-Qur’an dan Alkitab untuk merumuskan kriteria etik-legal yang relevan bagi instrumen keuangan kontemporer. Metode yang digunakan adalah pendekatan hermeneutik maʿna cum maghzā untuk menafsirkan ulang maksud riba. Tahap pertama berupa rekonstruksi makna tekstual dan kontekstual atas ayat kunci. Tahap kedua berupa jembatan analitik melalui temuan tafsir dan komentar klasik serta modern. Tahap ketiga berupa perumusan pesan substantif (maghzā) sebagai dasar evaluasi praktik keuangan. Hasil penelitian menunjukkan bahwa inti etis larangan riba terletak pada prinsip tidak menzalimi dan tidak dizalimi. Prinsip ini menolak bentuk bunga atau keuntungan yang bersifat eksploitatif dan yang memperberat beban debitur, serta tetap menjaga kekhasan ribā sebagai kategori etika dan hukum yang tidak dapat disamakan secara sederhana dengan istilah bunga. Studi ini menghasilkan indikator praktis untuk menilai keabsahan etis suatu kontrak yang mencakup keadilan pertukaran, proporsionalitas antara risiko dan imbal hasil, perlindungan bagi pihak yang rentan, pencegahan penggandaan utang yang memberatkan, serta transparansi informasi dan biaya. Temuan ini menegaskan orientasi maqāṣid asy-syarīʿah dengan penekanan pada perlindungan harta serta menawarkan kerangka evaluatif lintas teks suci yang dapat diadopsi dalam perancangan kontrak dan kebijakan keuangan syariah masa kini.